Negative electrode for secondary battery and secondary battery
Patent Information
- Application Number
- JP2023522238
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-18
- Filing Date
- 2022-02-22
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-02-22
Smart Images

Figure 0007639905000004 
Figure 0007639905000005 
Figure 0007639905000006
Abstract
Description
[Technical field]
[0001] The present technology relates to a negative electrode for a secondary battery and a secondary battery. [Background technology]
[0002] Due to the widespread use of various electronic devices such as mobile phones, secondary batteries have been developed as small, lightweight power sources that can provide high energy density. These secondary batteries include a positive electrode, a negative electrode, and an electrolyte, and various studies have been conducted on the structure of the secondary battery.
[0003] Specifically, a carbonaceous porous conductive substrate, a conductive agent (such as carbon nanotubes), and an active material (such as silicon) are used as materials for forming the negative electrode of a lithium-ion secondary battery, and the porosity (void ratio) of the negative electrode is specified (see, for example, Patent Document 1).
[0004] A conductive base material such as carbon fiber coated with silicon or the like is used as a material for forming the negative electrode of a lithium-ion secondary battery, and the silicon content (weight ratio) in the negative electrode is specified (see, for example, Patent Document 2).
[0005] A composite material containing a core (nanocarbon) and a shell (nanosilicon) is used as a material for forming the negative electrode of a lithium ion secondary battery, and the porosity of the composite material is specified (see, for example, Patent Document 3). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-335283 A [Patent Document 2] Special Publication No. 2015-531977 [Patent Document 3] Special Publication No. 2015-501279 Summary of the Invention
[0007] Although various studies have been conducted on the configuration of secondary batteries, the initial capacity characteristics, swelling characteristics and cycle characteristics of the secondary batteries are still insufficient, and there is room for improvement.
[0008] Therefore, there is a demand for a negative electrode for a secondary battery and a secondary battery that are capable of achieving excellent initial capacity characteristics, excellent swollenness characteristics, and excellent cycle characteristics.
[0009] A secondary battery negative electrode according to an embodiment of the present technology includes a plurality of first fiber parts, a plurality of coating parts, and a plurality of second fiber parts, and has a plurality of voids. The first fiber parts are connected to each other to form a three-dimensional network structure having a plurality of voids, and each of the first fiber parts includes carbon as a constituent element. Each of the coating parts coats a surface of each of the first fiber parts, and includes silicon as a constituent element. At least a part of the second fiber parts is connected to a surface of each of the coating parts, and each of the second fiber parts includes carbon as a constituent element. The first fiber parts have an average fiber diameter of 10 nm or more and 8000 nm or less, the second fiber parts have an average fiber diameter of 1 nm or more and 300 nm or less, and the porosity is 40 vol. % or more and 70 vol. % or less.
[0010] A secondary battery according to an embodiment of the present technology includes a positive electrode, a negative electrode, and an electrolyte, and the negative electrode has a configuration similar to that of the negative electrode for a secondary battery according to the embodiment of the present technology described above.
[0011] The details (definitions, calculation procedures, etc.) of the "average fiber diameter of the plurality of first fiber portions," "average fiber diameter of the plurality of second fiber portions," and "void ratio" will be described later.
[0012] According to the negative electrode for a secondary battery or the secondary battery of one embodiment of the present technology, the negative electrode for a secondary battery includes the above-mentioned multiple first fibrous parts, multiple covering parts, and multiple second fibrous parts, and has multiple voids. The above-mentioned conditions are satisfied for the average fiber diameter of the multiple first fibrous parts, the average fiber diameter of the multiple second fibrous parts, and the porosity, and therefore excellent initial capacity characteristics, excellent swollenness characteristics, and excellent cycle characteristics can be obtained.
[0013] Note that the effects of the present technology are not necessarily limited to the effects described here, but may be any of a series of effects related to the present technology described below. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic diagram illustrating a configuration of a negative electrode for a secondary battery according to an embodiment of the present technology. [Diagram 2] 2 is an enlarged cross-sectional view showing the configurations of a large diameter carbon fiber portion, a small diameter carbon fiber portion, and a coating portion shown in FIG. 1. [Diagram 3] 1 is a perspective view illustrating a configuration of a secondary battery according to an embodiment of the present technology. [Figure 4] 4 is an enlarged cross-sectional view showing the configuration of the battery element shown in FIG. [Diagram 5] 1 is a cross-sectional view illustrating a configuration of a secondary battery negative electrode according to Modification 1. FIG. [Figure 6] FIG. 1 is a block diagram showing a configuration of an application example of a secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present technology will be described in detail with reference to the drawings. The description will be given in the following order. 1. Negative electrode for secondary batteries 1-1.Configuration 1-2. Manufacturing method 1-3. Actions and Effects 2. Secondary battery 2-1.Configuration 2-2.Operation 2-3. Manufacturing method 2-4. Actions and Effects 3. Variations 4. Uses of secondary batteries
[0016] <1. Negative electrode for secondary batteries> First, a negative electrode for a secondary battery (hereinafter simply referred to as "negative electrode") according to one embodiment of the present technology will be described.
[0017] This negative electrode is used in a secondary battery, which is an electrochemical device. However, the negative electrode may be used in other electrochemical devices other than the secondary battery. The type of other electrochemical device is not particularly limited, but specifically, it is a capacitor or the like.
[0018] In addition, the negative electrode absorbs and releases an electrode reactant during an electrode reaction in an electrochemical device such as the secondary battery. The type of the electrode reactant is not particularly limited, but specifically, it is a light metal such as an alkali metal or an alkaline earth metal. The alkali metal is lithium, sodium, potassium, etc., and the alkaline earth metal is beryllium, magnesium, calcium, etc.
[0019] <1-1. Configuration> Fig. 1 is a schematic diagram of a negative electrode 10, which is an example of a negative electrode. Fig. 2 is an enlarged cross-sectional view of each of the large diameter carbon fiber portion 1, the small diameter carbon fiber portion 2, and the coating portion 3 shown in Fig. 1. However, Fig. 2 shows cross sections of each of the large diameter carbon fiber portion 1, the small diameter carbon fiber portion 2, and the coating portion 3 that intersect with the longitudinal direction of each of the large diameter carbon fiber portion 1 and the small diameter carbon fiber portion 2.
[0020] 1, the negative electrode 10 includes a plurality of large diameter carbon fiber portions 1, a plurality of small diameter carbon fiber portions 2, and a plurality of coating portions 3, and also has a plurality of voids 10G. That is, the negative electrode 10 does not include a current collector such as a metal foil (hereinafter referred to as a "metal current collector"), and is therefore a so-called metal current collector-less electrode.
[0021] [Multiple large diameter carbon fiber sections] As shown in Fig. 1, the large diameter carbon fiber portions 1 are a plurality of first fiber portions having an average fiber diameter AD1 larger than the average fiber diameter AD2 of the small diameter carbon fiber portions 2, and each of the large diameter carbon fiber portions 1 has a fiber diameter D1 as shown in Fig. 2. The large diameter carbon fiber portions 1 are connected to each other to form the above-mentioned three-dimensional network structure having the above-mentioned plurality of voids 10G.
[0022] 1, in order to simplify the illustration, each of the large diameter carbon fiber portions 1 is shown to be linear. However, the state (shape) of each of the large diameter carbon fiber portions 1 is not particularly limited, and may be curved or branched, or may be a mixture of two or more of these.
[0023] Here, as described above, the multiple large diameter carbon fiber parts 1 are connected to each other to form a three-dimensional network structure, more specifically, they are randomly entangled with each other. The multiple large diameter carbon fiber parts 1 may be bonded to each other via a carbide (not shown) such as a polymer compound, or may be connected to each other via one or more small diameter carbon fiber parts 2. As a result, the multiple large diameter carbon fiber parts 1 have multiple connection points, and the large diameter carbon fiber parts 1 are electrically connected to each other at the connection points.
[0024] The average fiber diameter AD1 of the plurality of large diameter carbon fiber parts 1 is 10 nm to 8000 nm. This is because the fiber diameter D1 becomes sufficiently large in the plurality of large diameter carbon fiber parts 1 which are the main parts of the negative electrode 10. As a result, a sufficient conductive network (three-dimensional mesh structure) is formed inside the negative electrode 10, and the conductivity of the negative electrode 10 is improved.
[0025] The procedure for calculating the average fiber diameter AD1 is as follows. First, the negative electrode 10 is collected, and then washed with a washing solvent such as dimethyl carbonate. When a secondary battery including the negative electrode 10 is obtained, the secondary battery is disassembled to collect the negative electrode 10. Next, the negative electrode 10 is cut using an ion milling device or the like to expose a cross section of the negative electrode 10.
[0026] Next, a cross section of the negative electrode 10 is observed using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) to obtain an observation result (observation image) of the cross section. This makes it possible to identify a plurality of large diameter carbon fiber parts 1 in the observation image. Observation conditions such as acceleration voltage and magnification can be set arbitrarily.
[0027] Next, 20 randomly selected large diameter carbon fiber portions 1 are measured for fiber diameter D1 of each of the 20 large diameter carbon fiber portions 1. Finally, the average value of the 20 fiber diameters D1 is calculated to obtain the average fiber diameter AD1.
[0028] There is no particular limitation on the average fiber length of each of the large diameter carbon fiber parts 1. This is because, as long as the large diameter carbon fiber parts 1 having the above-mentioned average fiber diameter AD1 are connected to each other, a sufficient conductive network (three-dimensional mesh structure) is formed regardless of the fiber length.
[0029] Each of the large diameter carbon fiber portions 1 contains carbon as a constituent element, and therefore contains a so-called carbon-containing material, which is a general term for materials that contain carbon as a constituent element.
[0030] Specifically, the large diameter carbon fiber parts 1 contain carbon paper because the large diameter carbon fiber parts 1 are sufficiently connected to each other and the average fiber diameter AD1 is sufficiently large, so that a sufficient conductive network (three-dimensional mesh structure) is formed.
[0031] However, the plurality of large diameter carbon fiber portions 1 may be a material in which a plurality of fibrous carbon materials having the above-mentioned average fiber diameter AD1 are processed to form a three-dimensional network structure. The type of this fibrous carbon material is not particularly limited, and specifically includes vapor grown carbon fiber (VGCF) and carbon nanofiber (CNF). In addition, the type of the fibrous carbon material may be a multi-walled carbon nanotube (multi-walled carbon nanotube (MWCNT)) such as a double-walled carbon nanotube (DWCNT).
[0032] [Multiple small diameter carbon fiber sections] The small diameter carbon fiber portions 2 are second fiber portions having an average fiber diameter AD2 smaller than the average fiber diameter AD1 of the large diameter carbon fiber portions 1 as shown in Fig. 1, and each of the small diameter carbon fiber portions 2 has a fiber diameter D2 as shown in Fig. 2. Here, each of the small diameter carbon fiber portions 2 is fixed to the surface of each of the covering portions 3, and is therefore connected to the surface of each of the covering portions 3.
[0033] 1, in order to simplify the illustration, the small diameter carbon fiber portions 2 are each shown as being linear. However, the state (shape) of each of the small diameter carbon fiber portions 2 is not particularly limited, as in the case of the state of the large diameter carbon fiber portions 1 described above.
[0034] The reason why the negative electrode 10 includes a plurality of small diameter carbon fiber parts 2 together with a plurality of large diameter carbon fiber parts 1 is that the plurality of large diameter carbon fiber parts 1 form a conductive network, and the plurality of small diameter carbon fiber parts 2 also form a dense conductive network, thereby significantly improving the conductivity of the negative electrode 10.
[0035] In particular, it is preferable that some or all of the multiple small diameter carbon fiber parts 2 (multiple small diameter carbon fiber parts 2R) are each connected to two or more coating parts 3, respectively. This is because the two or more coating parts 3 are electrically connected to each other via one or two or more small diameter carbon fiber parts 2R. This forms a denser conductive network, and the conductivity of the negative electrode 10 is further improved.
[0036] The average fiber diameter AD2 of the plurality of small diameter carbon fiber portions 2 is smaller than the average fiber diameter AD1 of the plurality of large diameter carbon fiber portions 1 described above, and specifically, is 1 / 10,000 to 1 / 2, and preferably 1 / 300 to 1 / 5, of the average fiber diameter AD1.
[0037] More specifically, the average fiber diameter AD2 is 1 nm to 300 nm. In a system in which a plurality of large diameter carbon fiber parts 1 and a plurality of small diameter carbon fiber parts 2 coexist, the average fiber diameter AD2 becomes sufficiently smaller than the average fiber diameter AD1, so that the plurality of small diameter carbon fiber parts 2 are easily dispersed inside the negative electrode 10. As a result, a dense conductive network is formed by the plurality of small diameter carbon fiber parts 2, and the conductivity of the negative electrode 10 is further improved.
[0038] The procedure for calculating the average fiber diameter AD2 is the same as the procedure for calculating the average fiber diameter AD1 described above, except that the fiber diameter D2 of each of any 20 small diameter carbon fiber portions 2 is measured, and the average value of the fiber diameters D2 of the 20 small diameter carbon fiber portions 2 is set as the average fiber diameter AD2. However, when the fiber diameter D2 is small, it is preferable to use a TEM rather than an SEM to observe the cross section of the negative electrode 10.
[0039] The average fiber length of each of the small diameter carbon fiber parts 2 is not particularly limited. This is because, as long as the small diameter carbon fiber parts 2 having the above-mentioned average fiber diameter AD2 are present inside the negative electrode 10, a dense conductive network is formed regardless of the fiber length.
[0040] Each of the plurality of small diameter carbon fiber portions 2 contains carbon as a constituent element, and therefore contains a carbon-containing material, similar to each of the plurality of large diameter carbon fiber portions 1.
[0041] Specifically, each of the small diameter carbon fiber parts 2 contains a fibrous carbon material such as a carbon nanotube, vapor grown carbon fiber (VGCF), or carbon nanofiber (CNF). This is because the small diameter carbon fiber parts 2 are easily dispersed sufficiently inside the negative electrode 10, and a dense conductive network is easily formed.
[0042] The type of carbon nanotube is not particularly limited, and may be a single-walled carbon nanotube (SWCNT) or a multi-walled carbon nanotube (MWCNT). A specific example of a multi-walled carbon nanotube is a double-walled carbon nanotube (DWCNT).
[0043] Among them, each of the small diameter carbon fiber parts 2 is preferably one or both of single-walled carbon nanotubes and vapor-grown carbon fibers. This is because the average fiber diameter AD2 becomes sufficiently small, so that the small diameter carbon fiber parts 2 are sufficiently dispersed inside the negative electrode 10 and a denser conductive network is formed.
[0044] [Multiple Covered Parts] As shown in FIG. 1, each of the multiple covering portions 3 covers the surface of each of the multiple large diameter carbon fiber portions 1, and as shown in FIG. 2, each has a thickness T1.
[0045] The covering portion 3 may cover the entire surface of the large diameter carbon fiber portion 1, or may cover only a part of the surface of the large diameter carbon fiber portion 1. In the latter case, the multiple covering portions 3 may cover the surface of the large diameter carbon fiber portion 1 at multiple locations spaced apart from one another. In FIG. 1, in order to simplify the contents of the drawing, a case is shown in which each of the multiple covering portions 3 covers the entire surface of each of the multiple large diameter carbon fiber portions 1.
[0046] As a result, each of the multiple large-diameter carbon fiber parts 1 having a relatively large average fiber diameter AD1 is covered on the surface with the covering part 3, while each of the multiple small-diameter carbon fiber parts 2 having a relatively small average fiber diameter AD2 is not covered on the surface with the covering part 3.
[0047] The average thickness AT1 of the multiple covering portions 3 is not particularly limited, but is preferably 2.8 nm to 1300 nm in particular. This is because the amount of the covering portion 3 covering the surface of the large diameter carbon fiber portion 1 is sufficiently large, so that the electrical conductivity of the negative electrode 10 is ensured and sufficient energy density can be obtained in the negative electrode 10.
[0048] The procedure for calculating the average thickness AT1 is as described below. First, the observation result (observation image) of the cross section of the negative electrode 10 is obtained by the same procedure as in the calculation of the average fiber diameter AD1 described above. Next, 20 covering portions 3 are arbitrarily selected, and the thickness T1 of each of the 20 covering portions 3 is measured. If the thickness T1 varies depending on the location in one covering portion 3, the maximum value of the thickness T1 is selected. Finally, the average value of the 20 thicknesses T1 is calculated to obtain the average thickness AT1.
[0049] Furthermore, each of the multiple covering portions 3 contains silicon as a constituent element and therefore contains a so-called silicon-containing material. This is because silicon has an excellent ability to absorb and release electrode reactants, and therefore a high energy density can be obtained.
[0050] This silicon-containing material is a general term for materials containing silicon as a constituent element. Therefore, the silicon-containing material may be elemental silicon, a silicon alloy, a silicon compound, a mixture of two or more of them, or a material containing one or more phases of them. However, elemental silicon may contain trace amounts of impurities. That is, the purity of elemental silicon does not have to be 100%. These impurities are impurities unintentionally contained in the manufacturing process of elemental silicon and oxides unintentionally formed due to oxygen in the atmosphere, etc. The content of impurities in elemental silicon is preferably as small as possible, and more preferably 5 wt% or less.
[0051] The silicon alloy contains, as constituent elements other than silicon, any one or more of metal elements such as tin, nickel, copper, iron, cobalt, manganese, zinc, indium, silver, titanium, germanium, bismuth, antimony, and chromium. The silicon compound contains, as constituent elements other than silicon, any one or more of non-metal elements such as carbon and oxygen. However, the silicon compound may further contain any one or more of the series of metal elements described for the silicon alloy as constituent elements other than silicon.
[0052] Specific examples of the silicon alloy are Mg2Si, Ni2Si, TiSi2, MoSi2, CoSi2, NiSi2, CaSi2, CrSi2, Cu5Si, FeSi2, MnSi2, NbSi2, TaSi2, VSi2, WSi2, ZnSi2, and SiC, etc. However, the composition of the silicon alloy (mixing ratio of silicon and metal elements) can be arbitrarily changed.
[0053] Specific examples of the silicon compound are SiB4, SiB6, Si3N4, Si2N2O, SiO v (0 < v ≦ 2) and LiSiO, etc. However, the range of v may be, for example, 0.2 < v < 1.4.
[0054] Among these, the silicon-containing material is preferably elemental silicon, since a higher energy density can be obtained. In this case, the silicon content in each of the multiple covering portions 3, i.e., the silicon content (purity) in the silicon-containing material, is not particularly limited, but is preferably 80% by weight or more, and more preferably 80% by weight to 100% by weight, since a significantly higher energy density can be obtained.
[0055] The weight percentage M (wt%), which is the ratio of the weight M3 of the multiple coating parts 3 to the sum of the weight M1 of the multiple large diameter carbon fiber parts 1, the weight M2 of the multiple small diameter carbon fiber parts 2, and the weight M3 of the multiple coating parts 3, is not particularly limited, but is preferably 40 wt% to 76 wt%. This is because the relationship between the weight of the carbon component (multiple large diameter carbon fiber parts 1 and multiple small diameter carbon fiber parts 2) and the weight of the silicon component (multiple coating parts 3) in the negative electrode 10 is optimized, so that sufficient energy density can be obtained while ensuring electrical conductivity. This weight percentage M is calculated based on the formula M=[M3 / (M1+M2+M3)]×100.
[0056] The procedure for calculating the weight ratio M is as follows. First, the negative electrode 10 is collected and then washed with a washing solvent such as dimethyl carbonate. Then, the negative electrode 10 is analyzed using thermogravimetric differential thermal analysis (TG-DTA) to determine the weights M1, M2, and M3. Any TG-DTA device can be used to analyze the negative electrode 10.
[0057] In the analysis of this negative electrode 10, the weight loss when the heating temperature is increased to about 450°C corresponds to the weight of the electrolyte and binder, and the weight loss when the heating temperature is increased to about 450°C to about 1350°C corresponds to the weights (weights M1 and M2) of the carbon components (plurality of large diameter carbon fiber parts 1 and plural small diameter carbon fiber parts 2). As a result, the weight of the remaining components corresponds to the weight (weight M3) of the silicon components (plurality of coating parts 3).
[0058] The temperature at which the weight loss due to the electrolyte is detected (approximately 450°C) may vary depending on the type of binder. Specifically, when the binder is polyvinylidene fluoride, the minimum value of the differential curve of the DTA is taken as the disappearance temperature, which is approximately 460°C.
[0059] Finally, the weight ratio M is calculated based on the weights M1, M2, and M3 according to the above formula.
[0060] Although not specifically shown here, a part or the whole of the surface of the covering portion 3 may be further covered with a covering layer. This covering layer contains one or more kinds of conductive materials such as carbon-containing materials and metal materials. This is because the conductivity of the negative electrode 10 is further improved. Details of the carbon-containing material are as described above. The type of the metal material is not particularly limited.
[0061] When forming this coating layer, a silane coupling agent, a polymer-based material, etc. are used in order to make it possible to sufficiently cover the surface of the coating part 3 with the coating layer. By sufficiently covering the surface of the coating part 3 with the coating layer, the decomposition reaction of the electrolyte on the surface of the coating part 3 containing the silicon-containing material is suppressed.
[0062] [Porosity] As described above, the negative electrode 10 includes a three-dimensional network structure formed by a plurality of large diameter carbon fiber portions 1, and therefore has a plurality of voids 10G.
[0063] The porosity R of the negative electrode 10 determined based on the plurality of voids 10G is 40 volume % to 70 volume %. Since the amount of the plurality of voids 10G present inside the negative electrode 10 is optimized, even if the coating portion 3 containing a silicon-containing material expands and contracts during charging and discharging, the internal stress (strain) caused by the expansion and contraction is appropriately alleviated by utilizing the plurality of voids 10G. As a result, the expansion and contraction of the coating portion 3 is suppressed even when charging and discharging are repeated, and deterioration of the negative electrode 10 is suppressed. The deterioration of the negative electrode 10 includes loss and cutting of the large diameter carbon fiber portion 1, loss and breakage of the small diameter carbon fiber portion 2, collapse and falling off of the coating portion 3, and the like.
[0064] The procedure for calculating the porosity R is as follows. After collecting and cleaning the negative electrode 10 using the same procedure as in the case of calculating the average fiber diameter AD1 described above, a three-dimensional image of the negative electrode 10 is obtained using a focused ion beam scanning electron microscope (FIB-SEM), and the porosity R is calculated based on the three-dimensional image using image analysis processing. In this image analysis processing, GeoDict, an innovative materials development comprehensive package software manufactured by Math2Market GmbH, or the like can be used.
[0065] [Other materials] Negative electrode 10 may further contain one or more of the other materials.
[0066] The type of the other material is not particularly limited, but specifically, it is a binder, etc. This is because the multiple large diameter carbon fiber parts 1, the multiple small diameter carbon fiber parts 2, and the coating part 3 are firmly connected to each other via the binder, thereby forming a strong conductive network.
[0067] The binder contains one or more of polymer compounds, and specific examples of the polymer compounds are polyimide, polyvinylidene fluoride, polyacrylic acid, styrene butadiene rubber, carboxymethyl cellulose, etc. When the negative electrode 10 contains a binder, some of the small diameter carbon fiber parts 2 may be free and not connected to the surface of the coating part 3.
[0068] <1-2. Manufacturing method> The negative electrode 10 is manufactured by the procedure described below. Here, the case where carbon paper is used as the plurality of large diameter carbon fiber parts 1 will be described.
[0069] First, prepare carbon paper that is a plurality of large diameter carbon fiber parts 1. In this carbon paper, a three-dimensional network structure is formed by connecting the plurality of large diameter carbon fiber parts 1 to each other, and thus a plurality of voids 10G are formed.
[0070] Next, a silicon-containing material is deposited on each surface of the large diameter carbon fiber portions 1 by using a gas phase method. The type of the gas phase method is not particularly limited, but specifically, it is any one or more of a vacuum deposition method, a chemical vapor deposition method (CVD) and a sputtering method. As a result, a coating portion 3 is formed on each surface of the large diameter carbon fiber portions 1, and the surface of each of the large diameter carbon fiber portions 1 is coated with the coating portion 3. In this case, the average thickness AT1 of the coating portions 3 can be controlled by adjusting the amount of deposition of the silicon-containing material.
[0071] By forming the multiple covering parts 3, the inner diameter of some or all of the multiple voids 10G decreases, and the porosity R before the multiple covering parts 3 are formed (so-called initial porosity R) decreases. However, if the initial porosity R is set to be sufficiently large, some or all of the multiple voids 10G will remain even after the multiple covering parts 3 are formed, and the porosity R can be calculated even after the multiple covering parts 3 are formed. In other words, the porosity R can be controlled by adjusting the deposition amount of the silicon-containing material.
[0072] As a method for forming the plurality of covering portions 3, a liquid phase method may be used instead of the gas phase method. The type of the liquid phase method is not particularly limited. Specifically, a solution containing polydihydrosilane or the like capable of forming metal silicon is applied to the surfaces of the plurality of large diameter carbon fiber portions 1, thereby impregnating the interiors of the plurality of large diameter carbon fiber portions 1 with the solution. However, the plurality of large diameter carbon fiber portions 1 may also be impregnated with the solution by immersing the plurality of large diameter carbon fiber portions 1 in a solution containing polydihydrosilane or the like. When carbon paper is used as the plurality of large diameter carbon fiber portions 1, the interior of the carbon paper is impregnated with the above-mentioned solution.
[0073] Next, a plurality of small diameter carbon fiber parts 2 are put into the solvent. As a result, the plurality of small diameter carbon fiber parts 2 are dispersed in the solvent, and a dispersion liquid is prepared. This solvent may be an aqueous solvent or a non-aqueous solvent (organic solvent). In this case, a binder may be added to the solvent. Details regarding this binder are as described above.
[0074] Next, the dispersion liquid is applied to the large diameter carbon fiber parts 1 on which the coating parts 3 are formed, and then the dispersion liquid is dried. As a result, the dispersion liquid containing the small diameter carbon fiber parts 2 is impregnated into the large diameter carbon fiber parts 1, and the small diameter carbon fiber parts 2 are fixed to the surfaces of the coating parts 3. Thus, the small diameter carbon fiber parts 2 are connected to the surfaces of the coating parts 3, and the negative electrode 10 is produced. However, the large diameter carbon fiber parts 1 on which the coating parts 3 are formed may be immersed in the dispersion liquid.
[0075] When connecting a plurality of small diameter carbon fiber parts 2 to the surfaces of a plurality of coating parts 3, instead of indirectly forming a plurality of small diameter carbon fiber parts 2 on the surfaces of a plurality of coating parts 3 using a dispersion liquid, a plurality of small diameter carbon fiber parts 2 may be directly formed on the surfaces of the plurality of coating parts 3. In this case, a metal catalyst is disposed on the surfaces of the plurality of coating parts 3, and then the plurality of small diameter carbon fiber parts 2 are grown using CVD. As a result, each of the plurality of small diameter carbon fiber parts 2 is firmly connected to the surfaces of the plurality of coating parts 3, and a strong conductive network is formed.
[0076] Finally, if necessary, the negative electrode 10 is pressed using a press or the like, and then the negative electrode 10 is fired. In this case, the porosity R can be controlled by adjusting the pressing pressure. The firing temperature can be set arbitrarily.
[0077] This completes the negative electrode 10, which includes a plurality of large diameter carbon fiber portions 1, a plurality of small diameter carbon fiber portions 2, and a plurality of coating portions 3, and has a plurality of voids 10G. When producing this negative electrode 10, the weight ratio M can be controlled by adjusting the deposition amount of the silicon-containing material and the concentration of the plurality of small diameter carbon fiber portions 2 in the dispersion liquid.
[0078] In addition, when producing the negative electrode 10, a papermaking process may be used after forming a plurality of large diameter carbon fiber parts 1 with a plurality of coating parts 3 formed thereon by the above-mentioned procedure, and then using the plurality of large diameter carbon fiber parts 1 with the plurality of coating parts 3 formed thereon and a plurality of small diameter carbon fiber parts 2. In this case, a wet process such as papermaking may be used, or a dry process using a web or the like may be used. In this case, a negative electrode 10 including a plurality of large diameter carbon fiber parts 1, a plurality of small diameter carbon fiber parts 2, and a plurality of coating parts 3 and having a plurality of voids 10G is produced.
[0079] <1-3. Actions and Effects> This negative electrode 10 includes a plurality of large diameter carbon fiber portions 1, a plurality of small diameter carbon fiber portions 2, and a plurality of coating portions 3, and has a plurality of voids 10G, each of the plurality of large diameter carbon fiber portions 1 and the plurality of small diameter carbon fiber portions 2 contains a carbon-containing material, each of the plurality of coating portions 3 contains a silicon-containing material, and the average fiber diameters AD1, AD2 and porosity R satisfy the above-mentioned conditions (AD1=10 nm to 8000 nm, AD2=1 nm to 300 nm, and porosity R=40 vol.% to 70 vol.%).
[0080] In this case, as described above, the average fiber diameters AD1, AD2 and the porosity R are each optimized, and therefore, a series of actions described below are obtained.
[0081] First, inside the negative electrode 10, a conductive network (three-dimensional mesh structure) is formed by a plurality of large diameter carbon fiber parts 1 containing a conductive carbon-containing material, and a dense conductive network is also formed by a plurality of small diameter carbon fiber parts 2 similarly containing a conductive carbon-containing material.
[0082] Secondly, since each of the plurality of covering portions 3 contains a silicon-containing material that is excellent in the ability to store and release an electrode reactant, a high energy density can be obtained.
[0083] Thirdly, even if each of the multiple coating parts 3 contains a silicon-containing material, the internal stress generated inside the negative electrode 10 during charging and discharging, i.e., during expansion and contraction of each of the multiple coating parts 3, is alleviated by utilizing the multiple voids 10G, and the expansion and contraction of the negative electrode 10 is suppressed. This suppresses deterioration of the negative electrode 10 caused by the internal stress generated during expansion and contraction of the multiple coating parts 3. In this case, even if the silicon content in the silicon-containing material is particularly large, the expansion and contraction of the negative electrode 10 is sufficiently suppressed, and therefore deterioration of the negative electrode 10 is effectively suppressed.
[0084] For these reasons, a high energy density can be obtained, expansion and contraction of the negative electrode 10 during charging and discharging is suppressed, and the discharge capacity is less likely to decrease even when charging and discharging are repeated. Therefore, a secondary battery using the negative electrode 10 can have excellent initial capacity characteristics, excellent swollenness characteristics, and excellent cycle characteristics.
[0085] In addition, since the above-mentioned negative electrode 10 does not require a metal current collector, it is possible to reduce the weight and increase the weight energy density (Wh / kg) compared to the case where a metal current collector is used.
[0086] In particular, when the weight ratio M is 40% by weight to 76% by weight, the relationship between the weight of the carbon component (the plurality of large diameter carbon fiber parts 1 and the plurality of small diameter carbon fiber parts 2) and the weight of the silicon component (the plurality of coating parts 3) in the negative electrode 10 is optimized. Therefore, sufficient energy density can be obtained while ensuring electrical conductivity, and thus a greater effect can be obtained.
[0087] Furthermore, when the average thickness AT1 of the multiple coating portions 3 is 2.8 nm to 1300 nm, the formation amount of each of the multiple coating portions 3 is sufficiently large while ensuring the electronic conductivity between the multiple large diameter carbon fiber portions 1. Therefore, a sufficient energy density can be obtained while ensuring the electrical conductivity, and thus a higher effect can be obtained.
[0088] Furthermore, if the silicon content in each of the multiple coating portions 3 (silicon-containing material) is 80% by weight or more, a significantly high energy density can be obtained while ensuring electrical conductivity, resulting in a greater effect.
[0089] Furthermore, if some or all of the multiple small diameter carbon fiber parts 2 are connected to two or more coating parts 3, the two or more coating parts 3 are electrically connected to each other via one or more small diameter carbon fiber parts 2. This forms a denser conductive network, thereby achieving a higher effect.
[0090] Here, when the porosity R has the above-mentioned large value (=40 volume % to 70 volume %), the conductive network is likely to become sparse. Moreover, since the coating portion 3 containing the silicon-containing material expands and contracts during the electrode reaction, the conductive network is likely to be disconnected. However, as described above, when some or all of the multiple small diameter carbon fiber portions 2 are connected to two or more coating portions 3, respectively, a dense conductive network is likely to be formed and the conductive network is unlikely to be disconnected.
[0091] Furthermore, if the large diameter carbon fiber parts 1 contain carbon paper, the large diameter carbon fiber parts 1 are sufficiently connected to each other and have a sufficiently large average fiber diameter AD1, so that a sufficient conductive network (three-dimensional mesh structure) is formed, resulting in a higher effect.
[0092] Furthermore, if the small-diameter carbon fiber parts 2 contain one or both of single-walled carbon nanotubes and vapor-grown carbon fibers, the average fiber diameter AD2 becomes sufficiently small. Therefore, the small-diameter carbon fiber parts 2 are easily dispersed sufficiently inside the negative electrode 10, and a denser conductive network is easily formed, so that a higher effect can be obtained.
[0093] <2. Secondary battery> Next, a secondary battery according to an embodiment of the present technology, more specifically, an example of a secondary battery using the above-described negative electrode 10 will be described.
[0094] The secondary battery described here is a secondary battery that obtains battery capacity by utilizing the occlusion and release of an electrode reactant, as described above, and includes a positive electrode, a negative electrode, a separator, and an electrolyte solution that is a liquid electrolyte. As described above, the type of the electrode reactant is not particularly limited.
[0095] In the following, an example will be given in which the electrode reactant is lithium. A secondary battery that obtains battery capacity by utilizing the absorption and release of lithium is a so-called lithium ion secondary battery. In this lithium ion secondary battery, lithium is absorbed and released in an ionic state.
[0096] In this case, the charge capacity of the negative electrode is larger than the discharge capacity of the positive electrode. That is, the electrochemical capacity per unit area of the negative electrode is set to be larger than the electrochemical capacity per unit area of the positive electrode. This is to prevent deposition of electrode reactants on the surface of the negative electrode during charging.
[0097] <2-1. Configuration> Fig. 3 shows a perspective configuration of a secondary battery. Fig. 4 shows an enlarged cross-sectional configuration of the battery element 30 shown in Fig. 3. However, Fig. 3 shows a state in which the exterior film 20 and the battery element 30 are separated from each other, and Fig. 4 shows only a part of the battery element 30. In the following, reference will be made from time to time to Figs. 1 and 2 already described, and the components of the negative electrode 10 already described will be cited.
[0098] 3 and 4, this secondary battery includes an exterior film 20, a battery element 30, a positive electrode lead 41, a negative electrode lead 42, and sealing films 51 and 52. The secondary battery described here is a laminate film type secondary battery that uses a flexible exterior film 20.
[0099] [Exterior film] 3, the exterior film 20 is a flexible exterior member that houses the battery element 30, and has a bag-like structure that is sealed when the battery element 30 is housed inside. Therefore, the exterior film 20 houses an electrolyte together with a positive electrode 31 and a negative electrode 32, which will be described later.
[0100] Here, the exterior film 20 is a single film-like member, and is folded in a folding direction F. This exterior film 20 is provided with a recessed portion 20U (so-called deep drawn portion) for accommodating the battery element 30.
[0101] Specifically, the exterior film 20 is a three-layer laminate film in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order from the inside, and when the exterior film 20 is folded, the outer peripheral edges of the opposing fusion layers are fused to each other. The fusion layer contains a polymer compound such as polypropylene. The metal layer contains a metal material such as aluminum. The surface protection layer contains a polymer compound such as nylon.
[0102] However, the configuration (number of layers) of the exterior film 20 is not particularly limited, and may be one or two layers, or may be four or more layers.
[0103] [Battery element] As shown in FIGS. 3 and 4, the battery element 30 is a power generating element including a positive electrode 31, a negative electrode 32, a separator 33, and an electrolyte (not shown), and is housed inside the exterior film 20.
[0104] Since this battery element 30 is a so-called laminated electrode body, the positive electrodes 31 and the negative electrodes 32 are laminated with a separator 33 interposed therebetween. The number of laminated positive electrodes 31, negative electrodes 32, and separators 33 is not particularly limited. Here, a plurality of positive electrodes 31 and a plurality of negative electrodes 32 are alternately laminated with the separators 33 interposed therebetween.
[0105] (positive electrode) As shown in FIG. 4, the positive electrode 31 includes a positive electrode current collector 31A and a positive electrode active material layer 31B.
[0106] Positive electrode current collector 31A has a pair of surfaces on which positive electrode active material layer 31B is provided. Positive electrode current collector 31A contains a conductive material such as a metal material, and a specific example of the metal material is aluminum.
[0107] As shown in Fig. 3, the positive electrode current collector 31A includes a protrusion 31AT on which the positive electrode active material layer 31B is not provided, and the protrusions 31AT are joined to each other to form a single lead. Here, the protrusion 31AT is integrated with the portion other than the protrusion 31AT. However, since the protrusion 31AT is separate from the portion other than the protrusion 31AT, it may be joined to the portion other than the protrusion 31AT.
[0108] The positive electrode active material layer 31B contains one or more types of positive electrode active materials capable of absorbing and releasing lithium. However, the positive electrode active material layer 31B may further contain one or more types of other materials such as a positive electrode binder and a positive electrode conductive agent.
[0109] Here, the positive electrode active material layer 31B is provided on both sides of the positive electrode current collector 31A. However, the positive electrode active material layer 31B may be provided on only one side of the positive electrode current collector 31A on the side where the positive electrode 31 faces the negative electrode 32. The method for forming the positive electrode active material layer 31B is not particularly limited, and specifically, it is any one or more types of coating methods and the like.
[0110] The type of the positive electrode active material is not particularly limited, but specifically includes a lithium-containing compound. The lithium-containing compound is a compound that contains one or more transition metal elements as constituent elements together with lithium, and may further contain one or more other elements as constituent elements. The type of the other elements is not particularly limited as long as it is an element other than lithium and transition metal elements, but specifically includes an element belonging to Groups 2 to 15 of the long periodic table. The type of the lithium-containing compound is not particularly limited, but specifically includes an oxide, a phosphate compound, a silicate compound, a borate compound, etc.
[0111] Specific examples of oxides are LiNiO2, LiCoO2, LiCo 0.98 Al 0.01 Mg 0.01 O2, LiNi0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.2 Mn 0.52 Co 0.175 Ni 0.1 O2, Li 1.15 (M 0.65 Ni 0.22 Co 0.13 )O2 and LiMn2O4. Specific examples of phosphate compounds include LiFePO4, LiMnPO4, LiFe 0.5 Mn 0.5 PO4 and LiFe 0.3 Mn 0.7 PO4, etc.
[0112] The positive electrode binder contains one or more of synthetic rubbers and polymeric compounds. Specific examples of synthetic rubbers include styrene-butadiene rubbers, fluorine-based rubbers, and ethylene-propylene-diene. Specific examples of polymeric compounds include polyvinylidene fluoride, polyimide, and carboxymethyl cellulose.
[0113] The positive electrode conductive agent contains one or more conductive materials such as carbon materials, and specific examples of the carbon materials are graphite, carbon black, acetylene black, ketjen black, carbon nanotubes, etc. However, the conductive material may also be a metal material, a polymer compound, etc.
[0114] (Negative electrode) As shown in FIG. 4, the negative electrode 32 faces the positive electrode 31 via a separator 33, and is capable of absorbing and releasing lithium. The negative electrode 32 has a configuration similar to that of the negative electrode 10 described above, and therefore includes a plurality of large diameter carbon fiber portions 1, a plurality of small diameter carbon fiber portions 2, and a plurality of coating portions 3. In the negative electrode 32, lithium is absorbed and released mainly in each of the plurality of coating portions 3. However, lithium may be absorbed and released not only in each of the plurality of coating portions 3, but also in one or both of the plurality of large diameter carbon fiber portions 1 and the plurality of small diameter carbon fiber portions 2.
[0115] As shown in FIG. 3, the negative electrode 32 includes a protrusion 31AT consisting of a portion of the large diameter carbon fiber portion 1 that is not provided with a plurality of covering portions 3, and the plurality of protrusions 31AT are joined to each other to form a single lead.
[0116] (Separator) 4, the separator 33 is an insulating porous film interposed between the positive electrode 31 and the negative electrode 32, and allows lithium ions to pass through while preventing contact (short circuit) between the positive electrode 31 and the negative electrode 32. This separator 33 contains a polymer compound such as polyethylene.
[0117] (electrolyte) The electrolyte is impregnated into each of the positive electrode 31, the negative electrode 32, and the separator 33, and contains a solvent and an electrolyte salt.
[0118] The solvent contains one or more of non-aqueous solvents (organic solvents) such as a carbonate ester compound, a carboxylate ester compound, and a lactone compound, and the electrolyte solution containing the non-aqueous solvent is a so-called non-aqueous electrolyte solution.
[0119] The carbonate ester compound includes cyclic carbonate esters and chain carbonate esters, etc. Specific examples of the cyclic carbonate esters include ethylene carbonate and propylene carbonate, etc. Specific examples of the chain carbonate esters include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, etc.
[0120] The carboxylate compound is a chain carboxylate, etc. Specific examples of the chain carboxylate are methyl acetate, ethyl acetate, trimethyl methyl acetate, methyl propionate, ethyl propionate, and propyl propionate.
[0121] The lactone compound is lactone, etc. Specific examples of lactone are γ-butyrolactone and γ-valerolactone, etc.
[0122] The electrolyte salt contains one or more kinds of light metal salts such as lithium salts.
[0123] Specific examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiN(FSO2)2), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalato)borate (LiB(C2O4)2), lithium difluoro(oxalato)borate (LiB(C2O4)F2), lithium monofluorophosphate (Li2PFO3), and lithium difluorophosphate (LiPF2O2).
[0124] The content of the electrolyte salt is not particularly limited, but specifically, it is 0.3 mol / kg to 3.0 mol / kg relative to the solvent, because high ionic conductivity can be obtained.
[0125] The electrode solution may further contain one or more of the additives, which are not particularly limited, and specifically include unsaturated cyclic carbonates, halogenated carbonates, phosphates, acid anhydrides, nitrile compounds, and isocyanate compounds.
[0126] Specific examples of unsaturated cyclic carbonates include vinylene carbonate, vinylethylene carbonate, and methyleneethylene carbonate. Specific examples of halogenated carbonates include halogenated cyclic carbonates and halogenated chain carbonates. Specific examples of halogenated cyclic carbonates include monofluoroethylene carbonate and difluoroethylene carbonate. Specific examples of halogenated chain carbonates include fluoromethylmethyl carbonate. Specific examples of phosphates include trimethyl phosphate and triethyl phosphate.
[0127] The acid anhydride includes dicarboxylic acid anhydride, disulfonic acid anhydride, and carboxylic acid sulfonic acid anhydride. A specific example of the dicarboxylic acid anhydride is succinic acid anhydride. A specific example of the disulfonic acid anhydride is ethanedisulfonic acid anhydride. A specific example of the carboxylic acid sulfonic acid anhydride is sulfobenzoic acid anhydride.
[0128] The nitrile compounds include mononitrile compounds, dinitrile compounds, and trinitrile compounds. A specific example of the mononitrile compound is acetonitrile. A specific example of the dinitrile compound is succinonitrile. A specific example of the trinitrile compound is 1,2,3-propanetricarbonitrile. A specific example of the isocyanate compound is hexamethylene diisocyanate.
[0129] [Positive lead] 3, the positive electrode lead 41 is a positive electrode terminal connected to a joint of the multiple protrusions 31AT of the positive electrode 31, and is led from the inside to the outside of the exterior film 20. The positive electrode lead 41 contains a conductive material such as a metal material, and a specific example of the metal material is aluminum. The shape of the positive electrode lead 41 is not particularly limited, and specifically, it is either a thin plate shape or a mesh shape.
[0130] [Negative lead] As shown in FIG. 3, the negative electrode lead 42 is a negative electrode terminal connected to a joint of a plurality of protrusions 32AT of the negative electrode 32, and is led from the inside to the outside of the exterior film 20. In particular, the negative electrode lead 42 is preferably connected to the large diameter carbon fiber portion 1 of the negative electrode 32. This is because the electrical conductivity between the negative electrode 32 and the negative electrode lead 42 is improved. The negative electrode lead 42 contains a conductive material such as a metal material, and a specific example of the metal material is copper. Here, the lead-out direction of the negative electrode lead 42 is the same as the lead-out direction of the positive electrode lead 41. The details of the shape of the negative electrode lead 42 are the same as the details of the shape of the positive electrode lead 41.
[0131] [Sealing film] The sealing film 51 is inserted between the exterior film 20 and the positive electrode lead 41, and the sealing film 52 is inserted between the exterior film 20 and the negative electrode lead 42. However, one or both of the sealing films 51 and 52 may be omitted.
[0132] The sealing film 51 is a sealing member that prevents outside air and the like from entering the inside of the exterior film 20. The sealing film 51 contains a polymer compound such as polyolefin that has adhesion to the positive electrode lead 41, and the polyolefin is polypropylene or the like.
[0133] The configuration of the sealing film 52 is similar to the configuration of the sealing film 51, except that the sealing film 52 is a sealing member having adhesion to the negative electrode lead 42. That is, the sealing film 52 contains a polymer compound such as polyolefin having adhesion to the negative electrode lead 42.
[0134] <2-2. Operation> When the secondary battery is charged, in the battery element 30, lithium is released from the positive electrode 31 and is absorbed in the negative electrode 32 via the electrolyte. On the other hand, when the secondary battery is discharged, in the battery element 30, lithium is released from the negative electrode 32 and is absorbed in the positive electrode 31 via the electrolyte. During these charging and discharging times, lithium is absorbed and released in an ionic state.
[0135] <2-3. Manufacturing method> When manufacturing a secondary battery, the positive electrode 31 and the negative electrode 32 are each produced and the electrolyte solution is prepared according to the procedure described below as an example, and then the secondary battery is assembled and subjected to a stabilization process after assembly.
[0136] [Preparation of positive electrode] First, a mixture (cathode mixture) in which a cathode active material, a cathode binder, and a cathode conductive agent are mixed together is poured into a solvent to prepare a paste-like cathode mixture slurry. This solvent may be an aqueous solvent or an organic solvent. Next, the cathode mixture slurry is applied to both sides (excluding the protrusions 31AT) of the cathode current collector 31A including the protrusions 31AT to form the cathode active material layer 31B. Finally, the cathode active material layer 31B is compression molded using a roll press or the like. In this case, the cathode active material layer 31B may be heated, or the compression molding may be repeated multiple times. As a result, the cathode active material layer 31B is formed on both sides of the cathode current collector 31A, and thus the cathode 31 is produced.
[0137] [Preparation of negative electrode] The negative electrode 32 including the protrusion 32AT is produced by a procedure similar to that for producing the negative electrode 10 described above.
[0138] [Preparation of electrolyte] An electrolyte salt is added to a solvent, whereby the electrolyte salt is dispersed or dissolved in the solvent, and an electrolyte solution is prepared.
[0139] [Secondary battery assembly] First, a laminate (not shown) is prepared by alternately laminating positive electrodes 31 and negative electrodes 32 with separators 33 interposed therebetween. This laminate has a similar configuration to that of the battery element 30, except that the positive electrodes 31, the negative electrodes 32, and the separators 33 are not impregnated with an electrolyte solution.
[0140] Next, the plurality of protruding portions 31AT are joined to one another, and the plurality of protruding portions 32AT are joined to one another. Next, the positive electrode lead 41 is joined to the joint of the plurality of protruding portions 31AT, and the negative electrode lead 42 is connected to the joint of the plurality of protruding portions 32AT.
[0141] Next, after the laminate is accommodated inside the recessed portion 20U, the exterior film 20 (adhesive layer / metal layer / surface protection layer) is folded to face the exterior films 20. Next, the outer peripheral edges of two sides of the opposing exterior films 20 (adhesive layers) are joined to each other using a heat fusion method or the like, thereby accommodating the laminate inside the bag-shaped exterior film 20.
[0142] Finally, after injecting an electrolyte solution into the bag-shaped exterior film 20, the outer peripheral edges of the remaining side of the exterior film 20 (adhesive layer) are joined together using a heat fusion method or the like. In this case, a sealing film 51 is inserted between the exterior film 20 and the positive electrode lead 41, and a sealing film 52 is inserted between the exterior film 20 and the negative electrode lead 42.
[0143] This causes the laminate to be impregnated with the electrolyte, producing a laminated electrode body, the battery element 30. Thus, the battery element 30 is sealed inside the bag-shaped exterior film 20, and a secondary battery is assembled.
[0144] [Stabilization of secondary batteries] The assembled secondary battery is charged and discharged. Various conditions such as the environmental temperature, the number of charge / discharge cycles (number of cycles), and the charge / discharge conditions can be set arbitrarily. As a result, a coating is formed on the surface of each of the positive electrode 31 and the negative electrode 32, so that the state of the secondary battery is electrochemically stabilized. Thus, the secondary battery is completed.
[0145] <2-4. Actions and Effects> In this secondary battery, the negative electrode 32 has a configuration similar to that of the above-described negative electrode 10. Therefore, for the same reasons as those described for the negative electrode 10, excellent initial capacity characteristics, excellent swollenness characteristics, and excellent cycle characteristics can be obtained.
[0146] Furthermore, if the secondary battery is a lithium ion secondary battery, a sufficient battery capacity can be stably obtained by utilizing the absorption and release of lithium, so that a higher effect can be obtained.
[0147] Other functions and effects of the secondary battery are similar to those of the negative electrode 10 described above.
[0148] <3. Modifications> Next, modified examples will be described.
[0149] The configurations of the negative electrode 10 and the secondary battery described above can be modified as appropriate, as described below, although the series of modifications described below may be combined with each other.
[0150] [Variation 1] As shown in Fig. 5, which corresponds to Fig. 2, the negative electrode 10 may further include a plurality of surface portions 4. Unlike Fig. 2, Fig. 5 shows only the surface portions 4 together with the large-diameter carbon fiber portion 1 and the covering portion 3.
[0151] Each of the surface portions 4 is provided on a surface of each of the coating portions 3, and has a thickness T2. Each of the surface portions 4 contains one or more types of ion conductive materials, which improves the ion conductivity of the negative electrode 10. The type of the ion conductive material is not particularly limited.
[0152] Specifically, the ion-conducting material is a solid electrolyte such as lithium oxynitride phosphate and lithium phosphate (Li3PO4). The composition of the lithium oxynitride phosphate is not particularly limited, but specifically, Li 3.30 PO 3.90 N 0.17 And so on.
[0153] The ion-conductive material is a gel electrolyte in which an electrolytic solution is held by a matrix polymer compound. The composition of the electrolytic solution is as described above. Specific examples of the matrix polymer compound include polyethylene oxide and polyvinylidene fluoride.
[0154] In particular, the ion conductive material preferably contains a solid electrolyte, that is, preferably contains one or both of lithium oxynitride phosphate and lithium phosphate, because this sufficiently improves the ion conductivity of the negative electrode 10.
[0155] The surface portion 4 may be provided on the entire surface of the covering portion 3, or may be provided on only a part of the surface of the covering portion 3. In the latter case, a plurality of surface portions 4 spaced apart from each other may be provided on the surface of the covering portion 3.
[0156] The average thickness AT2 of the multiple surface portions 4 is not particularly limited and can be set arbitrarily. The procedure for calculating the average thickness AT2 is the same as the procedure for calculating the average thickness AT1 described above, except that the thickness T2 of the surface portion 4 is measured instead of the thickness T1 of the covering portion 3.
[0157] The procedure for forming the multiple surface portions 4 is as described below. When a solid electrolyte is used as the ion-conductive material, the surface portion 4 is directly formed on the surface of the coating portion 3 by using a gas phase method such as a sputtering method. When a gel electrolyte is used as the ion-conductive material, a solution containing an electrolyte solution, a matrix polymer compound, and a dilution solvent is applied to the surface of the coating portion 3, and then the solution is dried. Details regarding the type of solvent are as described above. Note that after multiple small diameter carbon fiber portions 2 are connected to the surface of the coating portion 3, the coating portion 3 and the like may be immersed in the solution.
[0158] In this case, the ion conductivity of lithium ions is improved by utilizing a plurality of surface portions 4 inside the negative electrode 10, so that a higher effect can be obtained.
[0159] In particular, by utilizing a plurality of surface portions 4 containing an ion conductive material, the negative electrode 10 can be applied to an all-solid-state battery. This is because the expansion and contraction of the negative electrode 10 is suppressed, and therefore an increase in the interface resistance between the negative electrode 10 and the solid electrolyte is suppressed. This allows the all-solid-state battery to achieve both ensuring safety and improving energy density.
[0160] [Variation 2] A porous membrane separator 33 was used. However, although not specifically shown here, a laminated separator including a polymer compound layer may be used instead of the separator 33.
[0161] Specifically, the laminated separator includes a porous film having a pair of surfaces and a polymer compound layer provided on one or both surfaces of the porous film. This is because the adhesion of the separator to each of the positive electrode 31 and the negative electrode 32 is improved, thereby suppressing the winding deviation of the battery element 30. This makes it difficult for the secondary battery to swell even if a decomposition reaction of the electrolyte occurs. The configuration of the porous film is the same as that of the porous film described for the separator 33. The polymer compound layer includes a polymer compound such as polyvinylidene fluoride. This is because polyvinylidene fluoride and the like have excellent physical strength and are electrochemically stable.
[0162] Either or both of the porous film and the polymer compound layer may contain one or more of a plurality of insulating particles. This is because the insulating particles promote heat dissipation when the secondary battery generates heat, thereby improving the safety (heat resistance) of the secondary battery. The insulating particles are either or both of inorganic particles and resin particles. Specific examples of inorganic particles include particles of aluminum oxide, aluminum nitride, boehmite, silicon oxide, titanium oxide, magnesium oxide, and zirconium oxide. Specific examples of resin particles include particles of acrylic resin and styrene resin.
[0163] When preparing a laminated separator, a precursor solution containing a polymer compound and a solvent is prepared, and then the precursor solution is applied to one or both sides of a porous film. In this case, instead of applying the precursor solution to the porous film, the porous film may be immersed in the precursor solution. Also, a plurality of insulating particles may be contained in the precursor solution.
[0164] Even when this laminated separator is used, the same effect can be obtained because lithium ions are movable between the positive electrode 31 and the negative electrode 32. In this case, as described above, the safety of the secondary battery is particularly improved, and therefore, a higher effect can be obtained.
[0165] [Variation 3] An electrolyte solution, which is a liquid electrolyte, was used, but an electrolyte layer, which is a gel electrolyte, may be used instead of the electrolyte solution, although this is not specifically shown.
[0166] In the battery element 30 using an electrolyte layer, the positive electrode 31 and the negative electrode 32 are alternately laminated with the separator 33 and the electrolyte layer interposed therebetween. In this case, the electrolyte layer is interposed between the positive electrode 31 and the separator 33, and the electrolyte layer is interposed between the negative electrode 32 and the separator 33. However, the electrolyte layer may be interposed only between the positive electrode 31 and the separator 33, or may be interposed only between the negative electrode 32 and the separator 33.
[0167] Specifically, the electrolyte layer contains a polymer compound together with an electrolyte solution, and the electrolyte solution is held by the polymer compound. This is because leakage of the electrolyte solution is prevented. The composition of the electrolyte solution is as described above. The polymer compound contains polyvinylidene fluoride and the like. When forming the electrolyte layer, a precursor solution containing an electrolyte solution, a polymer compound, and a dilution solvent is prepared, and then the precursor solution is applied to one or both sides of each of the positive electrode 31 and the negative electrode 32. Details regarding the type of solvent are as described above.
[0168] Even when this electrolyte layer is used, the same effect can be obtained because lithium ions can move between the positive electrode 31 and the negative electrode 32 via the electrolyte layer. In this case, leakage of the electrolyte is particularly prevented as described above, so that a higher effect can be obtained.
[0169] <4. Uses of secondary batteries> Finally, uses (application examples) of the secondary battery will be described.
[0170] The use of the secondary battery is not particularly limited. The secondary battery used as a power source may be a main power source for electronic devices and electric vehicles, or may be an auxiliary power source. The main power source is a power source that is used preferentially regardless of the presence or absence of other power sources. The auxiliary power source is a power source that is used instead of the main power source, or a power source that is switched from the main power source.
[0171] Specific examples of uses of secondary batteries are as follows: Electronic devices such as video cameras, digital still cameras, mobile phones, notebook computers, headphone stereos, portable radios, and portable information terminals. Storage devices such as backup power sources and memory cards. Power tools such as power drills and power saws. Battery packs mounted on electronic devices. Medical electronic devices such as pacemakers and hearing aids. Electric vehicles such as electric cars (including hybrid cars). Power storage systems such as home or industrial battery systems that store power in preparation for emergencies. In these uses, one secondary battery may be used, or multiple secondary batteries may be used.
[0172] The battery pack may use a single cell or a battery pack. The electric vehicle is a vehicle that operates (runs) using a secondary battery as a driving power source, and may be a hybrid vehicle equipped with a driving source other than the secondary battery. In a home power storage system, it is possible to use home electrical appliances by utilizing the power stored in the secondary battery, which is a power storage source.
[0173] Here, an example of an application of the secondary battery will be specifically described. The configuration described below is merely an example and can be modified as appropriate.
[0174] Figure 6 shows the block configuration of a battery pack. The battery pack described here is a battery pack (a so-called soft pack) that uses one secondary battery, and is installed in electronic devices such as smartphones.
[0175] 6, the battery pack includes a power source 61 and a circuit board 62. The circuit board 62 is connected to the power source 61, and includes a positive terminal 63, a negative terminal 64, and a temperature detection terminal 65.
[0176] The power source 61 includes one secondary battery. In this secondary battery, a positive electrode lead is connected to a positive electrode terminal 63, and a negative electrode lead is connected to a negative electrode terminal 64. This power source 61 is connected to the outside via the positive electrode terminal 63 and the negative electrode terminal 64, and is therefore capable of charging and discharging. The circuit board 62 includes a control unit 66, a switch 67, a thermosensitive resistor (PTC) element 68, and a temperature detection unit 69. However, the PTC element 68 may be omitted.
[0177] The control unit 66 includes a central processing unit (CPU) and a memory, and controls the operation of the entire battery pack. The control unit 66 detects and controls the usage state of the power source 61 as necessary.
[0178] When the voltage of the power source 61 (secondary battery) reaches the overcharge detection voltage or the overdischarge detection voltage, the control unit 66 turns off the switch 67 to prevent a charging current from flowing through the current path of the power source 61. The overcharge detection voltage is not particularly limited, but specifically, is 4.2±0.05V, and the overdischarge detection voltage is not particularly limited, but specifically, is 2.4±0.1V.
[0179] The switch 67 includes a charge control switch, a discharge control switch, a charge diode, and a discharge diode, and switches between the presence and absence of a connection between the power source 61 and an external device in response to an instruction from the control unit 66. The switch 67 includes a field effect transistor (MOSFET) using a metal oxide semiconductor, and the charge / discharge current is detected based on the ON resistance of the switch 67.
[0180] The temperature detection unit 69 includes a temperature detection element such as a thermistor, measures the temperature of the power supply 61 using the temperature detection terminal 65, and outputs the temperature measurement result to the control unit 66. The temperature measurement result measured by the temperature detection unit 69 is used when the control unit 66 performs charge / discharge control in the event of abnormal heat generation, and when the control unit 66 performs correction processing when calculating the remaining capacity. EXAMPLES
[0181] An embodiment of the present technology will be described.
[0182] <Examples 1 to 14 and Comparative Examples 1 to 7> After the secondary batteries were fabricated, the characteristics of the secondary batteries were evaluated. Here, in order to evaluate the characteristics of the secondary batteries, two types of secondary batteries (a first secondary battery and a second secondary battery) were fabricated.
[0183] [Preparation of the first secondary battery] First secondary batteries (Examples 1 to 14 and Comparative Examples 4 to 7) were fabricated according to the procedure described below. The first secondary batteries were laminate film-type lithium ion secondary batteries (battery capacity = 7 mAh to 12 mAh) shown in Figs. 3 and 4.
[0184] In the following description, the components of the negative electrode 10 shown in FIGS. 1 and 2 will be referenced from time to time to explain the process of producing the negative electrode 32.
[0185] (Preparation of positive electrode) First, the positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 A positive electrode mixture was prepared by mixing 97 parts by mass of ethylenediaminetetraacetate (O2), 2.2 parts by mass of a positive electrode binder (polyvinylidene fluoride), and 0.8 parts by mass of a positive electrode conductive agent (Ketjen black). Next, the positive electrode mixture was put into a solvent (N-methyl-2-pyrrolidone, an organic solvent), and then the solvent was stirred using a rotation and revolution mixer to prepare a paste-like positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to both sides (excluding the protrusions 31AT) of the positive electrode current collector 31A (aluminum foil, thickness = 15 μm) including the protrusions 31AT using a coating device, and then the positive electrode mixture slurry was dried (drying temperature = 120 ° C.) to form the positive electrode active material layer 31B. Finally, the positive electrode active material layer 31B was compression molded using a hand press machine (volume density of the positive electrode active material layer 31B = 3.5 g / cm 3 ) In this way, the positive electrode 31 including the protrusion 31AT was produced.
[0186] (Preparation of negative electrode) First, carbon paper (CP, thickness = 50 μm) was prepared, which is a plurality of large diameter carbon fiber parts 1 including protrusions 32AT. This carbon paper has a three-dimensional mesh structure formed by the plurality of large diameter carbon fiber parts 1, and therefore has a plurality of voids 10G. The inner diameter of each of the plurality of voids 10G is larger than the inner diameter of the negative electrode 32 after completion. The average fiber diameter AD1 (nm) of the plurality of large diameter carbon fiber parts 1 is as shown in Tables 1 and 2.
[0187] Next, a silicon-containing material (elemental silicon (Si)) was deposited by vacuum deposition on each surface (excluding the protruding portion 32AT) of the large diameter carbon fiber portions 1 to form the multiple coating portions 3. In this case, silicon (purity = 99.9%) was used as the deposition source, and two deposition sources were arranged to sandwich the large diameter carbon fiber portions 1, with the deposition rate = 90 nm / min and the basis weight of the silicon-containing material = 2.0 mg / cm. 2 The average thickness AT1 (nm) of the coating 3 is as shown in Tables 1 and 2.
[0188] Next, 16 parts by mass of the small diameter carbon fiber parts 2 (single-walled carbon nanotubes (SWCNTs) or vapor-grown carbon fibers (VGCF)) and 84 parts by mass of a binder (polyvinylidene fluoride) were added to a solvent (N-methyl-2-pyrrolidone, an organic solvent), and the solvent was stirred to prepare a dispersion. The average fiber diameter AD2 (nm) of the small diameter carbon fiber parts 2 is as shown in Tables 1 and 2.
[0189] Next, the dispersion liquid was applied to the plurality of large diameter carbon fiber parts 1 (excluding the protruding parts 32AT) on which the plurality of covering parts 3 were formed, so that the dispersion liquid was impregnated into the three-dimensional network structure formed by the plurality of large diameter carbon fiber parts 1. As a result, the plurality of small diameter carbon fiber parts 2 were fixed (connected) to the surfaces of the plurality of covering parts 3, and thus the negative electrode 32 including the protruding parts 32AT was produced. In this case, the basis weight of the plurality of small diameter carbon fiber parts 2=0.02 mg / cm 2 It was decided.
[0190] Finally, the negative electrode 32 was pressed in a room temperature environment (temperature = 23 ° C.), and then heated in a nitrogen (N2) atmosphere (heating temperature = 350 ° C., heating time = 3 hours). In this case, the porosity R (volume %) was changed by adjusting the pressing pressure as shown in Tables 1 and 2.
[0191] In this way, a negative electrode 32 was completed, which included a plurality of large diameter carbon fiber parts 1, a plurality of small diameter carbon fiber parts 2, and a plurality of coating parts 3, and also had a plurality of voids 10G. When producing this negative electrode 32, the weight percentage M (% by weight) was changed as shown in Tables 1 and 2 by adjusting the deposition amount of the silicon-containing material and the concentration of the plurality of small diameter carbon fiber parts 2 in the dispersion liquid.
[0192] (Preparation of electrolyte) After adding an electrolyte salt (lithium hexafluorophosphate) to the solvent, the solvent was stirred. The solvent used was ethylene carbonate, which is a cyclic carbonate ester, dimethyl carbonate, which is a chain carbonate ester, and monofluoroethylene carbonate, which is an additive (halogenated cyclic carbonate ester). The mixing ratio (weight ratio) of the solvents was ethylene carbonate:dimethyl carbonate:monofluoroethylene carbonate=30:60:10. The content of the electrolyte salt was 1 mol / kg relative to the solvent. In this way, an electrolytic solution was prepared.
[0193] (Assembly of the first secondary battery) First, a positive electrode 31 including a protrusion 31AT and a negative electrode 32 including a protrusion 32AT were laminated together via a separator 33 (microporous polyethylene film, thickness = 20 μm) to produce a laminate (positive electrode 31 / separator 33 / negative electrode 32).
[0194] Subsequently, a positive electrode lead 41 (aluminum foil) was joined to the protruding portion 31AT, and a negative electrode lead 42 (copper foil) was joined to the protruding portion 32AT.
[0195] Next, the exterior film 20 (adhesive layer / metal layer / surface protection layer) was folded so as to sandwich the laminate housed inside the recessed portion 20U, and then the outer peripheral edges of two sides of the exterior film 20 (adhesive layer) were heat-sealed to each other to house the laminate inside the bag-shaped exterior film 20. As the exterior film 20, an aluminum laminate film was used in which a adhesive layer (polypropylene film, thickness = 30 μm), a metal layer (aluminum foil, thickness = 40 μm), and a surface protection layer (nylon film, thickness = 25 μm) were laminated in this order from the inside.
[0196] Finally, after injecting an electrolyte solution into the bag-shaped exterior film 20, the outer peripheral edges of the remaining side of the exterior film 20 (bonding layer) were heat-sealed to each other in a reduced pressure environment. In this case, a sealing film 51 (polypropylene film, thickness = 5 μm) was inserted between the exterior film 20 and the positive electrode lead 41, and a sealing film 52 (polypropylene film, thickness = 5 μm) was inserted between the exterior film 20 and the negative electrode lead 42.
[0197] As a result, the laminate was impregnated with the electrolyte, producing the battery element 30. Thus, the battery element 30 was enclosed inside the exterior film 20, and a first secondary battery was assembled.
[0198] When assembling the first secondary battery, the thickness of the positive electrode active material layer 31B was adjusted so that the capacity ratio, i.e., the ratio of the positive electrode charge capacity to the negative electrode charge capacity (=positive electrode charge capacity / negative electrode charge capacity), was 0.7.
[0199] (Stabilization of the first secondary battery) The first secondary battery was charged and discharged for one cycle in a room temperature environment (temperature = 23°C). During charging, the battery was charged at a constant current of 0.1C until the voltage reached 4.2V, and then was charged at a constant voltage of 4.2V until the current reached 0.025C. During discharging, the battery was discharged at a constant current of 0.1C until the voltage reached 2.0V. 0.1C is the current value at which the battery capacity (theoretical capacity) is fully discharged in 10 hours, and 0.025C is the current value at which the battery capacity is fully discharged in 40 hours.
[0200] As a result, a coating was formed on the surface of each of the positive electrode 31 and the negative electrode 32, and the state of the first secondary battery was electrochemically stabilized. Thus, the first secondary battery was completed.
[0201] [Preparation of the second secondary battery] A second secondary battery (battery capacity=10 mAh to 15 mAh) was produced in the same manner as the first secondary battery described above, except that a lithium metal plate (thickness=100 μm) was used instead of the positive electrode 31.
[0202] Here, the first secondary battery using the positive electrode 31 as a counter electrode for the negative electrode 32 is a so-called full cell, whereas the second secondary battery using a lithium metal plate as a counter electrode for the negative electrode 32 is a so-called half cell.
[0203] [Preparation of a secondary battery for comparison] For comparison, two types of secondary batteries for comparison (Comparative Examples 1 and 2) were produced in the same manner, except that a comparative negative electrode was produced using a metal current collector.
[0204] To prepare this negative electrode, first, 82 parts by mass of a negative electrode active material (silicon (Si), purity=95%, median diameter D50=50 nm), 10 parts by mass (solid content equivalent) of a negative electrode binder (polyimide), 3 parts by mass of a negative electrode conductive agent (carbon black), and 5 parts by mass of another negative electrode conductive agent (carbon nanotube dispersion) were mixed together to obtain a negative electrode mixture. This carbon nanotube dispersion contained 0.8 parts by mass of carbon nanotubes (the above-mentioned multiple small diameter carbon fiber parts 2) and 4.2 parts by mass of a dispersion medium (polyvinylidene fluoride).
[0205] Next, the negative electrode mixture was added to a solvent (organic solvent N-methyl-2-pyrrolidone), and the organic solvent was stirred using a planetary mixer to prepare a paste-like negative electrode mixture slurry. Next, the negative electrode mixture slurry was applied to both sides of a negative electrode current collector (copper foil (Cu), thickness = 10 μm or 6 μm), which is a metal current collector, using a coating device, and then the negative electrode mixture slurry was dried to form a negative electrode active material layer. This produced the negative electrode.
[0206] Finally, the negative electrode was pressed in a room temperature environment (temperature = 23 ° C.), and then heated in a nitrogen atmosphere (heating temperature = 350 ° C., heating time = 3 hours). In this case, the porosity R of the negative electrode active material layer was changed by adjusting the pressing pressure, as shown in Tables 1 and 2.
[0207] In addition, the column "Metal current collector (thickness)" shown in each of Tables 1 and 2 indicates whether or not a metal current collector was used, and if so, the material and thickness (μm) of the metal current collector.
[0208] For comparison, two types of secondary batteries for comparison (Comparative Example 3) were produced in the same manner except that the multiple small diameter carbon fiber parts 2 were not used.
[0209] [Characteristic evaluation of secondary batteries] The characteristics of the secondary battery (initial capacity characteristics, swelling characteristics, and cycle characteristics) were evaluated, and the results shown in Tables 1 and 2 were obtained.
[0210] In this case, the second secondary battery (half cell) was used to evaluate the initial capacity characteristics, and the first secondary battery (full cell) was used to evaluate the swelling characteristics and cycle characteristics, according to the procedures described below.
[0211] (Initial capacity characteristics) The discharge capacity was measured by charging and discharging the secondary battery for one cycle while applying pressure to the secondary battery in a room temperature environment (temperature = 23 ° C.) From this, the initial capacity, which is an index for evaluating the initial capacity characteristics, was calculated based on the formula: initial capacity (mAh / g) = discharge capacity (mAh) / total weight (g) of the negative electrode 32.
[0212] In this case, pressure was applied to the secondary battery in the direction in which the positive electrode 31 and the negative electrode 32 were stacked together with the separator 33 interposed therebetween, so that the secondary battery was charged and discharged while the positive electrode 31 and the negative electrode 32 were in close contact with each other through the separator 33. Note that the above-mentioned total weight of the negative electrode 32 includes the weight of a metal current collector when one is used, whereas it does not include the weight of the metal current collector when no metal current collector is used.
[0213] During charging, the battery was charged at a constant current of 0.1 C until the voltage reached 0.005 V, and then charged at a constant voltage of 0.005 V until the current reached 0.01 C. During discharging, the battery was discharged at a constant current of 0.1 C until the voltage reached 1.5 V. 0.01 C is the current value at which the battery capacity is fully discharged in 100 hours.
[0214] (Swelling characteristics) First, the thickness of the secondary battery (thickness before charging) was measured in a room temperature environment (temperature = 23°C).
[0215] Next, the secondary battery was charged while a pressure was being applied to the secondary battery, and then the thickness of the secondary battery (thickness after charging) was measured.
[0216] In this case, similarly to the case of evaluating the initial capacity characteristics described above, pressure was applied to the secondary battery to cause the positive electrode 31 and the negative electrode 32 to come into close contact with each other via the separator 33, and the secondary battery was charged. During charging, the battery was charged at a constant current of 0.1 C until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.01 C.
[0217] Finally, the swelling ratio, which is an index for evaluating the swelling characteristics, was calculated based on the formula: swelling ratio (%)=[(thickness after charging−thickness before charging) / thickness before charging]×100.
[0218] (Cycle characteristics) First, the secondary battery was charged and discharged one cycle in a room temperature environment (temperature=23) to measure the discharge capacity (discharge capacity at the first cycle).
[0219] During charging, the battery was charged at a constant current of 0.5 C until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.025 C. During discharging, the battery was discharged at a constant current of 0.5 C until the voltage reached 2.5 V. 0.5 C is the current value that fully discharges the battery capacity in 2 hours.
[0220] Next, in the same environment, the secondary battery was charged and discharged 199 cycles under the same charge and discharge conditions to measure the discharge capacity (discharge capacity at the 200th cycle).
[0221] Finally, the capacity retention rate, which is an index for evaluating cycle characteristics, was calculated based on the formula: Capacity retention rate (%)=(Discharge capacity at 200th cycle / Discharge capacity at 1st cycle)×100.
[0222] (Standardization of characteristic values) The initial capacity values shown in Tables 1 and 2 are normalized values with the initial capacity value for the secondary battery of Comparative Example 1 using a metal current collector (copper foil with a thickness of 10 μm) set to 100. The same applies to the values of the swollenness rate and capacity retention rate, which are normalized based on the secondary battery of Comparative Example 1.
[0223] [Table 1]
[0224] [Table 2]
[0225] [Consideration] As shown in Tables 1 and 2, the initial capacity, the swollenness rate, and the capacity retention rate each varied greatly depending on the configuration of the negative electrode. In the following, the initial capacity, the swollenness rate, and the capacity retention rate each value in Comparative Example 1 are used as the comparison standard.
[0226] Specifically, when a metal current collector was used, decreasing the thickness of the metal current collector (Comparative Example 2) increased the initial capacity, but increased the swollenness rate and decreased the capacity retention rate.
[0227] In contrast, when multiple large diameter carbon fiber sections 1, multiple small diameter carbon fiber sections 2, and multiple coating sections 3 were used without using a metal collector (Examples 1 to 14 and Comparative Examples 4 to 7), the initial capacity, swelling ratio, and capacity retention rate each varied depending on the configuration.
[0228] That is, when either the average fiber diameters AD1, AD2 or the porosity R was outside the appropriate range (Comparative Examples 4 to 7), two types of trends were obtained. Specifically, the swelling ratio decreased, but either the initial capacity or the capacity retention ratio decreased. Alternatively, the swelling ratio decreased, and the initial capacity and the capacity retention ratio each increased, but the capacity retention ratio did not increase sufficiently.
[0229] However, when the average fiber diameters AD1, AD2 and the porosity R were each within an appropriate range (AD1 = 10 nm to 8000 nm, AD2 = 1 nm to 300 nm, R = 40 volume % to 70 volume %) (Examples 1 to 14), the swelling rate decreased and the initial capacity and capacity retention rate both increased, and the capacity retention rate was sufficiently increased.
[0230] In this case, when the weight ratio M was 40% by weight to 76% by weight, the swelling ratio was sufficiently reduced, and the initial capacity and the capacity retention ratio were each sufficiently increased. Also, when the average thickness AT was 2.8 nm to 1300 nm, the swelling ratio was sufficiently reduced, and the initial capacity and the capacity retention ratio were each sufficiently increased.
[0231] In addition, when multiple large diameter carbon fiber parts 1 and multiple coating parts 3 were used but multiple small diameter carbon fiber parts 2 were not used (Comparative Example 3), the swelling rate decreased and the initial capacity increased, but the capacity retention rate decreased.
[0232] <Examples 15 and 16> As shown in Table 3, a secondary battery was produced in the same manner as in Example 1, except that multiple surface portions 4 containing an ion-conductive material were formed in the production process of the negative electrode 32, and then the characteristics of the secondary battery (initial capacity characteristics, swelling characteristics, and cycle characteristics) were evaluated.
[0233] As an ion-conducting material, lithium phosphate oxynitride (Li 3.30 PO 3.90 N 0.17 ) and lithium phosphate (Li3PO4). The average thickness AT2 (nm) of the multiple surface portions 4 is as shown in Table 3.
[0234] When forming a plurality of surface portions 4, a sputtering method was used to deposit an ion conductive material on the surface of the covering portion 3. However, when forming the surface portion 4 containing lithium phosphate, lithium phosphate was used as a target, whereas when forming the surface portion 4 containing lithium oxynitride phosphate, lithium phosphate was used as a target in a nitrogen atmosphere.
[0235] [Table 3]
[0236] As shown in Table 3, when multiple surface portions 4 were formed (Examples 15 and 16), the capacity retention rate was increased while minimizing the decrease in initial capacity and the increase in swelling rate, compared to the case where the multiple surface portions 4 were not formed (Example 1).
[0237] [summary] From the results shown in Tables 1 to 3, when the negative electrode 32 (negative electrode 10) contains a plurality of large diameter carbon fiber parts 1, a plurality of small diameter carbon fiber parts 2, and a plurality of coating parts 3 and has a plurality of voids 10G, each of the plurality of large diameter carbon fiber parts 1 and the plurality of small diameter carbon fiber parts 2 contains a carbon-containing material, each of the plurality of coating parts 3 contains a silicon-containing material, and the above-mentioned appropriate conditions are satisfied for the average fiber diameters AD1, AD2 and the porosity R, the initial capacity and capacity retention rate each increase and the swell rate decreases. Therefore, excellent initial capacity characteristics, excellent swell characteristics, and excellent cycle characteristics can be obtained in the secondary battery.
[0238] Although the present technology has been described above with reference to an embodiment and examples, the configuration of the present technology is not limited to the configuration described in the embodiment and examples and can be modified in various ways.
[0239] Specifically, the secondary battery has been described as having a laminate film type battery structure. However, the battery structure of the secondary battery is not particularly limited, and may be other battery structures such as a cylindrical type, a square type, a coin type, and a button type.
[0240] Also, the battery element has been described as having a stacked structure. However, the structure of the battery element is not particularly limited, and may be other structure such as a wound type or a zigzag type. In the wound type, the positive electrode and the negative electrode are wound with a separator interposed therebetween, and in the zigzag type, the positive electrode and the negative electrode are folded in a zigzag shape while facing each other with the separator interposed therebetween.
[0241] Furthermore, although the electrode reactant is lithium, the electrode reactant is not particularly limited. Specifically, the electrode reactant may be other alkali metals such as sodium and potassium, as described above, or alkaline earth metals such as beryllium, magnesium, and calcium. In addition, the electrode reactant may be other light metals such as aluminum.
[0242] The effects described in this specification are merely examples, and the effects of the present technology are not limited to the effects described in this specification. Therefore, other effects may be obtained with respect to the present technology.
Claims
1. A positive electrode and a negative electrode including a plurality of first fiber portions, a plurality of covering portions, and a plurality of second fiber portions, and having a plurality of voids; Electrolyte and Equipped with the first fiber parts are connected to each other to form a three-dimensional network structure having the plurality of voids, and are electrically conductive to each other; and each of the first fiber parts contains carbon as a constituent element; each of the plurality of covering portions covers a surface of each of the plurality of first fiber portions, has an ability to occlude and release an electrode reactant, and contains silicon as a constituent element; at least a portion of the second fiber portions is connected to a surface of each of the coating portions, the coating portions are electrically connected to each other via at least one of the second fiber portions, and each of the second fiber portions contains carbon as a constituent element; The average fiber diameter of the plurality of first fiber portions is 10 nm or more and 8000 nm or less, The average fiber diameter of the plurality of second fiber portions is 1 nm or more and 300 nm or less, an average fiber diameter of the second fiber portions is smaller than an average fiber diameter of the first fiber portions; The porosity of the negative electrode is 40% by volume or more and 70% by volume or less. Secondary battery.
2. A ratio of the weight of the plurality of covering portions to the sum of the weight of the plurality of first fiber portions, the weight of the plurality of covering portions, and the weight of the plurality of second fiber portions is 40% by weight or more and 76% by weight or less. The secondary battery according to claim 1 .
3. The average thickness of the plurality of coating portions is 2.8 nm or more and 1300 nm or less. The secondary battery according to claim 1 or 2.
4. The silicon content in each of the plurality of coating portions is 80% by weight or more. The secondary battery according to claim 1 .
5. At least a portion of the plurality of second fiber portions is connected to each of the two or more covering portions. The secondary battery according to claim 1 .
6. the plurality of first fiber portions include carbon paper, Each of the second fiber portions includes at least one of a single-walled carbon nanotube and a vapor-grown carbon fiber. The secondary battery according to claim 1 .
7. The negative electrode further includes a plurality of surface portions provided on the surfaces of the plurality of covering portions, Each of the plurality of surface portions includes an ion-conductive material. The secondary battery according to claim 1 .
8. The ion-conducting material includes at least one of lithium oxyphosphate and lithium phosphate. The secondary battery according to claim 7.
9. It is a lithium-ion secondary battery. The secondary battery according to claim 1 .
10. The fiber optic cable includes a plurality of first fiber portions, a plurality of covering portions, and a plurality of second fiber portions, and has a plurality of voids; the first fiber parts are connected to each other to form a three-dimensional network structure having the plurality of voids, and are electrically conductive to each other; and each of the first fiber parts contains carbon as a constituent element; the plurality of covering portions cover surfaces of the plurality of first fiber portions, have an ability to occlude and release an electrode reactant, and contain silicon as a constituent element; at least a portion of the second fiber portions is connected to a surface of each of the coating portions, the coating portions are electrically connected to each other via at least one of the second fiber portions, and each of the second fiber portions contains carbon as a constituent element; The average fiber diameter of the plurality of first fiber portions is 10 nm or more and 8000 nm or less, The average fiber diameter of the plurality of second fiber portions is 1 nm or more and 300 nm or less, an average fiber diameter of the second fiber portions is smaller than an average fiber diameter of the first fiber portions; The porosity is 40% by volume or more and 70% by volume or less. Negative electrode for secondary batteries.
Citation Information
Patent Citations
Anode active material, its manufacturing method, and anode and lithium cell using this anode active material
JP2006173121A
Nonaqueous electrolyte secondary battery
JP2007335283A
Negative electrode active material for lithium ion battery, and its manufacturing method, cathode for lithium ion battery, and lithium ion battery
JP2008066128A
Negative electrode material for lithium ion secondary battery, method of producing negative electrode material for lithium ion secondary battery and lithium ion secondary battery
JP2013089403A
Methods for preparing silicon / carbon composite materials, materials prepared thereby, and electrodes containing such materials, particularly negative electrodes.
JP2015501279A